Downregulation of Melanoma Cell Adhesion Molecule (MCAM/CD146) Accelerates Cellular Senescence in Human Umbilical Cord Blood‐Derived Mesenchymal Stem Cells. (3rd March 2016) - Jin, Hye Jin; Kwon, Ji Hye; Kim, Miyeon; Bae, Yun Kyung; Choi, Soo Jin; Oh, Wonil; Yang, Yoon Sun; Jeon, Hong Bae
Abstract : CD146 expression is gradually decreased during the long‐term expansion of human umbilical cord blood‐derived mesenchymal stem cells (hUCB‐MSCs) in culture, and enforced CD146 downregulation accelerated senescence in hUCB‐MSCs, which affected their multilineage differentiation potential, growth, and stemness. These data indicate a possible role for CD146 in inhibiting senescence in hUCB‐MSCs, which may occur via the regulation of Bmi‐1, Id1, and Twist1 expression. CD146 may be a novel marker for predicting senescence in hUCB‐MSCs, and it could be valuable in quality‐control assessments and for improving the therapeutic potential of hUCB‐MSC‐based therapy. Abstract : Therapeutic applications of mesenchymal stem cells (MSCs) for treating various diseases have increased in recent years. To ensure that treatment is effective, an adequate MSC dosage should be determined before these cells are used for therapeutic purposes. To obtain a sufficient number of cells for therapeutic applications, MSCs must be expanded in long‐term cell culture, which inevitably triggers cellular senescence. In this study, we investigated the surface markers of human umbilical cord blood‐derived MSCs (hUCB‐MSCs) associated with cellular senescence using fluorescence‐activated cell sorting analysis and 242 cell surface‐marker antibodies. Among these surface proteins, we selected the melanoma cell adhesion molecule (MCAM/CD146) for further study with the aim of validating observed expression differences and investigating the associated implications in hUCB‐MSCs during cellular senescence. We observed that CD146 expression markedly decreased in hUCB‐MSCs following prolonged in vitro expansion. Using preparative sorting, we found that hUCB‐MSCs with high CD146 expression displayed high growth rates, multilineage differentiation, expression of stemness markers, and telomerase activity, as well as significantly lower expression of the senescence markers p16, p21, p53, and senescence‐associated β‐galactosidase, compared with that observed in hUCB‐MSCs with low‐level CD146 expression. In contrast, CD146 downregulation with small interfering RNAs enhanced the senescence phenotype. In addition, CD146 suppression in hUCB‐MSCs caused downregulation of other cellular senescence regulators, including Bmi‐1, Id1, and Twist1. Collectively, our results suggest that CD146 regulates cellular senescence; thus, it could be used as a therapeutic marker to identify senescent hUCB‐MSCs. Significance: One of the fundamental requirements for mesenchymal stem cell (MSC)‐based therapies is the expansion of MSCs during long‐term culture because a sufficient number of functional cells is required. However, long‐term growth inevitably induces cellular senescence, which potentially causes poor clinical outcomes by inducing growth arrest and the loss of stem cell properties. Thus, the identification of markers for evaluating the status of MSC senescence during long‐term culture may enhance the success of MSC‐based therapy. This study provides strong evidence that CD146 is a novel and useful marker for predicting senescence in human umbilical cord blood‐derived MSCs (hUCB‐MSCs), and CD146 can potentially be applied in quality‐control assessments of hUCB‐MSC‐based therapy.